Work Environment And Work Stress on Employee Performance in Dalton Hotel Makassar - Wahyudi Wahyudi; Suriyanti Mangkona (Sains: Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine and analyze the effect of work environment and work stress on employee performance at Hotel Dalton, Makassar. The research approach used is a quantitative approach with an explanatory method—sampling using a simple random sampling technique, with a total of 137 employees as respondents. The statistical method used in this study is multiple linear regression. The results of the analysis show that the work environment variable does not have a partial effect on employee performance, but the work stress variable has a partial effect on employee performance variables. Furthermore, work environment and work stress have a simultaneous influence on employee performance at Hotel Dalton, Makassar